THE ROLES OF SOPHIE NEVEU AS REFLECTION OF WOMEN’S EQUALITY IN DAN BROWN’S THE DA VINCI CODE NOVEL - Rahayu Rini; Pepi Siti Paturohmah; Ujang Suyatman (Universitas Islam Negeri Sunan Gunung Djati, 2019)
This research analyzes women‘s issues in The Da Vinci Code novel by Dan Brown. In the novel there is a female character named Sophie Neveu . Sophie's role as a woman who can be relied upon in various situations makes her considered as woman who carries the spirit of feminism. The researchers decided to examine the role of Sophie Neveu as reflection of women's equality in The Da Vinci Code novel. The main theory used is Liberal Feminism by Betty Friedan. The form used in this research is qualitative and descriptive method in process of data analysis. The results of the discussion of this research are 1). Sophie Neveu play eleven roles of masculine qualities i.e. strong woman, competitive, courageous, unyielding, confident, independent, adventurous, aggressive, assertive, intelligent and generally acting as leaders, and; 2). The factors that make Sophie Neveu able to play this role is the background of her education. The conclusions of this research are masculine characteristics that can be owned by women and men, to become advanced individuals, women as part of the community must have equal opportunities as men in getting equal education, and the last that education is very important.Keywords: Characterization, Women‘s issues, Women equality, Liberal feminism, Masculine qualities